Jelinekius prisniyi sp. nov., new species of genus Jelinekius Majer, 1990 (Coleoptera: Dasytidae: Rhadalinae) from Tajikistan - Kovalenko, Yakov N. (Zootaxa, 2017)
The genus Jelinekius Majer, 1990, previously known only from Iran, is reported from Tajikistan for the first time. A new species, J. prisniyi sp. nov., is described as new to science.